Dietary carbohydrate, muscle glycogen content, and endurance performance in well-trained women - Walker, J. L.; Heigenhauser, G. J. F.; Hultman, E.; Spriet, L. L. (Journal of Applied Physiology, 2000)
This study examined the ability of well-trained eumenorrheic women to increase muscle glycogen content and endurance performance in response to a high-carbohydrate diet (HCD; ~78% carbohydrate) compared with a moderate-carbohydrate diet (MD; ~48% carbohydrate) when tested during the luteal phase of the menstrual cycle. Six women cycled to exhaustion at ~80% maximal oxygen uptake (O2 max) after each of the randomly assigned diet and exercise-tapering regimens. A biopsy was taken from the vastus lateralis before and after exercise in each trial. Preexercise muscle glycogen content was high after the MD (625.2 ± 50.1 mmol/kg dry muscle) and 13% greater after the HCD (709.0 ± 44.8 mmol/kg dry muscle). Postexercise muscle glycogen was low after both trials (MD, 91.4 ± 34.5; HCD, 80.3 ± 19.5 mmol/kg dry muscle), and net glycogen utilization during exercise was greater after the HCD. The subjects also cycled longer at ~80% O2 max after the HCD vs. MD (115:31 ± 10:47 vs. 106:35 ± 8:36 min:s, respectively). In conclusion, aerobically trained women increased muscle glycogen content in response to a high-dietary carbohydrate intake during the luteal phase of the menstrual cycle, but the magnitude was smaller than previously observed in men. The increase in muscle glycogen, and possibly liver glycogen, after the HCD was associated with increased cycling performance to volitional exhaustion at ~80% O2 max.